2003
DOI: 10.1097/01.ta.0000046253.33495.70
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism in Trauma: A Local Manifestation of Systemic Hypercoagulability?

Abstract: Although elevated in seriously injured patients, neither markers of activated coagulation nor specific injury patterns are predictive of VTE. Associations with immobilization and obesity suggest that VTE after injury is a systemic hypercoagulable disorder with local manifestations of thrombosis related to lower extremity stasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 37 publications
3
86
0
2
Order By: Relevance
“…It remains to be further established whether additional indirect effects of RNA may contribute to its procoagulant function. Despite the rapid degradation of RNA, the apparent procoagulant sensitization of plasma or whole blood could contribute to the as yet poorly understood hypercoagulable state observed in patients under thrombotic risk (36). Under conditions of tissue injury in association with sepsis, bacterial or viral infections, the expected increase of extracellular RNA may very well be related to the prothrombotic state in the affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be further established whether additional indirect effects of RNA may contribute to its procoagulant function. Despite the rapid degradation of RNA, the apparent procoagulant sensitization of plasma or whole blood could contribute to the as yet poorly understood hypercoagulable state observed in patients under thrombotic risk (36). Under conditions of tissue injury in association with sepsis, bacterial or viral infections, the expected increase of extracellular RNA may very well be related to the prothrombotic state in the affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Meissner et al [24] analysed markers of the clotting system in 101 trauma patients, and found significantly elevated F1 þ 2 levels on admission. The levels remained elevated throughout the first month of follow-up, indicating an activation of the clotting system.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of studies have demonstrated a pronounced imbalance between proand anticoagulatory factors in the setting of trauma, e.g. upregulation of tissue factor (TF) and markers of thrombin generation [19,[24][25][26] and simultaneous reduction of natural anticoagulants/fibrinolytic factors such as antithrombin (AT), protein C (PC), and protein S (PS) [25,26]. However, to which extent the posttraumatic hypofibrinolytic state contributes to this hypercoagulability with all its deleterious clinical consequences remains unclear [18,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,4,5 Limited data suggest that patients with penetrating injuries have a lower risk of thrombosis than those who sustain blunt trauma.…”
Section: Major Traumamentioning
confidence: 99%